Kajian terhadap Perbankan Syariah dalam Konsep Fiqih Ekonomi - Dastiana, Fuja; Wira, Ahmad; Duhriah , Duhriah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the relationship between the concept of economic jurisprudence and Islamic banking practices in Indonesia. Economic jurisprudence, as part of Islamic teachings, emphasizes the principles of justice, benefit, and honesty in economic activities, which serve as the normative basis for Islamic financial management. With the rapid development of the Islamic banking industry in Indonesia, it is important to examine the extent to which the principles of economic jurisprudence have been consistently implemented in the operations of Islamic financial institutions. This study used a literature study method (library research) by analyzing various sources, such as books on Islamic jurisprudence (fiqh muamalah), scientific journals, fatwas from the National Sharia Council (DSN-MUI), and regulations from the Financial Services Authority (OJK). The results of the study indicate that Islamic banking in Indonesia has implemented the principles of economic jurisprudence through contracts such as mudharabah, musyarakah, murabahah, and ijarah. However, challenges remain in the form of low public literacy and the need to align the theoretical concepts of economic jurisprudence with modern financial practices. Therefore, strengthening the understanding and application of the values ​​of Islamic economic jurisprudence is necessary to ensure the sustainability and integrity of the Islamic banking system in Indonesia.